Revitalisasi Zakat Produktif dalam Maqasid Asy-Syari’ah Ibnu ‘Asyur: Strategi Penguatan Ekonomi Umat di Era Digital - Saifullah, Saifullah; Wasik, Abdul (IAIN Langsa, 2024)
This study aims to analyze the concept of revitalizing productive zakat from the perspective of Maqasid Asy-Syari’ah according to Ibnu ‘Asyur and to formulate strategies for strengthening the economic empowerment of the Muslim community in the digital era. The benefits of this research include academic contributions to enriching the discourse on Islamic economics and practical advantages for zakat management institutions in developing a more transparent, fair, and inclusive distribution system through the utilization of digital technology. This article falls under library research with a qualitative approach, employing a descriptive analytical study methodology to examine the relevance of productive zakat in the context of the digitalization of the Islamic economy. The findings indicate that the revitalization of productive zakat from Ibnu Asyur's perspective not only emphasizes the five core concepts of Maqasid Syariah but also integrates three of his unique concepts: al-‘adalah (justice), al-ḥurriyah (freedom), and al-musāwah (equality). The strategy for strengthening the Muslim economy through digitalization, according to Ibnu Asyur, remains highly relevant, particularly in ensuring a more transparent, inclusive, and equitable distribution of zakat to achieve sustainable prosperity.